Gambaran Pola Makan dan Tingkat Kecemasan pada Mahasiswa Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung Semarang - Marga Putri Ayu Lestari Ningsih; Moch. Aspihan; Iskim Luthfa (Pusat Riset dan Inovasi Nasional, 2025)
Eating patterns and anxiety are two interrelated aspects, especially among students. This anxiety can affect various aspects of students' lives, including their eating patterns. A healthy diet is very important for college students because it contributes to their physical and mental health. However, many students have difficulty maintaining a balanced diet. Several factors that influence students' eating patterns include limited time, irregular eating habits. On the other hand, high levels of anxiety among college students are often related to academic pressure, social problems, and mental health. The aim of this research is to determine the description of eating patterns and anxiety levels among students at the Faculty of Nursing, Sultan Agung Islamic University, Semarang. This type of research is quantitative with a quantitative descriptive design, data collection carried out by this researcher using consecutive sampling, on a sample of 244 respondents. From the results of the 244 research respondents, the majority of respondents were 19 years old, 73 students (29.9%), female, 197 students (80.7%), the majority of respondents were 3rd semester students, totaling 96 students (39.3%). The results of this research show that the eating patterns of some students, 205 students (84.0%) have good eating patterns and the anxiety level of students in the moderate category is 144 students (59.0%). From these results it can be concluded that there is a picture of eating patterns and anxiety levels in students at the Faculty of Nursing, Sultan Agung Islamic University, Semarang.